Consumer Perception, Awareness, and Satisfaction about Goods and Services Tax (GST): With reference to Kalaburagi District (Global Journal of Management and Business Research, 2022)
Goods and Services Tax (GST) was implemented in India with the primary objective to reduce the burden on all stakeholders in the economy. Consumers are the vital stakeholders of GST as they bear the burden of taxes indirectly and contribute to government exchequer. Before introduction of GST, there were many taxes in force, which led to more complexities in taxing taxpayers, and there was a problem of cascading taxes. GST came as a hope to overcome the issues of earlier tax systems and provide many benefits to consumers. The paper examines consumers perception, level of awareness, and satisfaction about GST. To achieve the objectives of the study online survey has been undertaken by randomly sharing survey links to consumers of Kalaburagi district of Karnataka state. Non-parametric test has been used to analyze the primary data collected. The Chi-square test has been used to test consumers perception, and Mann witney U test and Kruskal-Wallis tests have been used to test the significance of two or more samples. Correlation has been used to examine correlation between demographic variables and level of awareness. The study's findings reveal that consumers have a moderate level of awareness about GST, and level of awareness depends upon educational qualifications of respondents. majority of respondents have a positive perception towards, and most of the consumers are satisfied with working of GST system. There is a need to increase awareness among consumers by increasing promotional activities and by introducing GST as a course in undergraduate and postgraduate studies.
Keywords: GST; consumer awareness; perceptions; satisfaction; consumer education